The status of cryptocurrency in Morocco - Zakaria Bziker (Research in Globalization, 2021)
Cryptocurrency is a new economy of transacting value whose use case is undeniable. Its only requirement is to be human, and it is borderless. In Morocco, cryptocurrency is erasing borders and gaining popularity. However, the general public opinion on this new innovation is unclear. This study aims to elucidate the popularity of this technology in the Kingdom by means of a small survey. The present study also investigates areas related to cryptocurrency, such as people's trust in banks. The results from the survey are contrasted with other countries to obtain a global perspective regarding Morocco's placement in the cryptocurrency adoption spectrum. The results also suggest that Morocco has the potential to adopt this technology. Notably, 9% of the sample population claim that they have owned, or still own, some sort of cryptocurrency. However, the country faces legal obstructions and financial restrictions that impede the progress of cryptocurrency adoption.
Keywords: 330; Cryptocurrency; Morocco; Blockchain technology; Bitcoin; Decentralization; Global economy; Distributed